Reduced Cytokine Tumour Necrosis Factor by Pharmacological Intervention in a Preclinical Study - Armin Mooranian; Jacqueline Chester; Edan Johnston; Corina Mihaela Ionescu; Daniel Walker; Melissa Jones; Susbin Raj Wagle; Bozica Kovacevic; Thomas Foster; Momir Mikov; Hani Al-Salami (Biomolecules, 2022)
Recent preclinical studies in our laboratory have shown that the bile acid profile is altered during diabetes development and such alteration has been linked to the diabetes-associated inflammatory profile. Hence, this study aimed to investigate if the first-line antidiabetic drug metformin will alter the bile acid profile and diabetes-associated inflammation in a murine model of pre-type 2 diabetes. C57 mice were randomly allocated into three equal groups of eight. Group One was given a low-fat diet (LFD), Group Two was given a high-fat diet (HFD), and Group Three was given an HFD and, upon prediabetes confirmation, daily oral metformin for one month. Blood glucose, glycated haemoglobin, drug concentrations in tissues and faeces, and the inflammatory and bile acid profiles were measured. Metformin showed wide tissue distribution and was also present in faeces. The bile acid profile showed significant alteration due to prediabetes, and although metformin did not completely normalize it, it did exert significant effects on both the bile acid and the inflammatory profiles, suggesting a direct and, to some extent, positive impact, particularly on the diabetes-associated inflammatory profile.